Students’ Reading Skill In Digital Literacy Through Weblog At SMK Negeri 3 Kupang - Ainah Bt Abdullah; Sukardi Weda; Rampeng Rampeng (Jounal of Primary Education, 2023)
this study. This research was conducted from November 2022 to December 2022. This study was categorized as a quasi-experimental research project. There were 38 students from Class TKJ who were the control group, and 37 students from Class TKJ 4 who were the experimental group, totaling 75 students. Students in the experimental group were explained about the Digital Literacy Through Weblog, while those in the control group were explained lightly. The pre-test and post-test methods were used to get the data. Both groups took the pre-test before the therapy, and both groups took the post-test following the treatment. The T-test was used to assess the data from the pre-test and post-test for both groups. The result of the research shows that the difference in reading ability between the students taught digital literacy through and those taught without digital literacy through weblog is significant. It can be seen in the result of the hypothesis testing